Chapter 22: The cooperation dilemma: can agricultural cooperatives sustainably survive in a globalised food system while contributing to food security? - Ajates, Raquel (Edward Elgar Publishing, 2023)
This chapter explores, analysing the case of Spain, the often-held assumption that a strong agricultural cooperative sector in a country correlates with robust food security. The Mediterranean country has a strong agricultural cooperative sector, being one of the top co-operators in farming in Europe. Spain is consistently ranked as the second country in terms of the number of agricultural cooperatives and the third in terms of members and employees. Data on both the agricultural cooperative sector and on food insecurity levels in Spain are presented and discussed. The findings indicate a tension between cooperative principles and the market pressures these farmers' organisations face to survive in a globalised food system, in a context of rural depopulation and raising production and distribution costs. These tensions raise complex questions on the ability of agricultural cooperatives to contribute to food security and sustainability, such as: food security, a global or national endeavour? Security for consumers or for producers? These tensions are explored, alongside a reflection on the different types of agricultural cooperative models and the socio-economic and environmental impacts of their structure, growth models and activities. Particular attention is paid to multi-stakeholder cooperatives, communal land use cooperatives and micro-cooperatives in the context of food security and sustainability. The chapter ends with some conclusions and policy recommendations.